# C1 ProblemWatch

Announcements
This discussion is closed.
#1
Find , as surds, the roots of the equation

2(x+1)(x-4)-(x-2)^2=0

I was not that sure on how to approach this question, so I just expanded out of the brackets and then use the quadratic formulae. But still got it wrong.

Any ideas? Thanks
0
14 years ago
#2
2x^2 - 6x - 8 - x^2 + 4x - 4 = 0
x^2 - 2x -12 = 0
x = (2 +/- rt52)/2
x = 1 +/- rt13
0
#3
(Original post by C4>O7)
2x^2 - 6x - 8 - x^2 + 4x - 4 = 0
x^2 - 2x -12 = 0
x = (2 +/- rt52)/2
x = 1 +/- rt13
Thanks, however how did you get sqrt 12, as sqrt52/2 is not 13 but 26
0
14 years ago
#4
x = (2 +/- rt52)/2
x = [2 +/- root(13*4)]/2
x = [2 +/- 2root13]/2
x = 1 +/- root13
0
#5
(Original post by Widowmaker)
x = (2 +/- rt52)/2
x = [2 +/- root(13*4)]/2
x = [2 +/- 2root13]/2
x = 1 +/- root13
Oh so thats what he did, turned it into a surd.
0
X
new posts
Back
to top
Latest
My Feed

### Oops, nobody has postedin the last few hours.

Why not re-start the conversation?

see more

### See more of what you like onThe Student Room

You can personalise what you see on TSR. Tell us a little about yourself to get started.

### University open days

• Bournemouth University
Midwifery Open Day at Portsmouth Campus Undergraduate
Wed, 16 Oct '19
• Teesside University
Wed, 16 Oct '19
• University of the Arts London
London College of Fashion – Cordwainers Footwear and Bags & Accessories Undergraduate
Wed, 16 Oct '19

### Poll

Join the discussion

#### How has the start of this academic year been for you?

Loving it - gonna be a great year (109)
17.99%
It's just nice to be back! (163)
26.9%
Not great so far... (217)
35.81%
I want to drop out! (117)
19.31%